ACCOUNTING OF LOST PROFITS AS A RESULT OF MILITARY ACTIONS BY AGRIBUSINESS ENTERPRISES - BURDYM, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the issue of accounting for lost profits in agribusiness enterprises because of military operations. Agrarian enterprises suffer direct losses in the form of damage and destruction of assets and indirect losses in the form of reduced crop areas, lower yields of long-term biological assets of crop production, lower prices due to the inability to export crops, and higher prices for inputs. All damages incurred should be reimbursed by the aggressor country, so it is necessary to ensure that they are properly reflected in the accounting. The current legal framework contains various definitions of lost profits and mostly operates with the concepts of unearned income and profit. It is substantiated that the lost profit in war time is precisely the unearned income and cannot be equated with unearned profit, since this may reduce the amount of damage caused to an enterprise. At the same time, the current Methodology for Determining Damage and the Amount of Losses provides for the determination of lost profits only in respect of property involved in commercial activities for the purpose of generating profit or income. However, not all assets may be involved in commercial activities. Having considered the definition of “enterprise” and “entrepreneurship”, it is proposed to calculate the amount of lost profits not by the type of property, but by the unit that generates cash flows. The author considers the issue of initial data for determining the lost profit in case of impossibility to use a land plot and damage to long-term biological assets. The author proposes to account for the lost profit to be reimbursed by the guilty party on account 075 “Lost profit of the enterprise as a result of military aggression”. To ensure a timely and complete recording of lost profits in accounting, the author has developed a primary document and a consolidated accounting register. In addition, the author considers possible scenarios of repayment of losses incurred by agricultural enterprises (voluntary payment, recovery by court decision, payment from the state budget, at the expense of funds from the compensation fund). The author proposes a scheme of postings for reflecting transactions in accounting, depending on which scenario of repayment of lost profits will be used.